Smart object counter - Pong, Jeremy Zhi Jun (Nanyang Technological University, 2023)
Counting people from surveillance videos, counting cells from microscopic images are very tedious and time-consuming work for human being. In this project, a software will be developed to localize and count the objects with similar characteristic in the image or video. We may assumed that the object is known with some prior knowledge for machine learning. However, objects may have some variations from the image due to size, lighting, perspective view issue, overlapping issue etc.